The Risk of Diabetic Peripheral Neuropathy among Patients with Type 2 Diabetes Mellitus in Urban and Rural Areas - Qona'ah, Arina; Pratiwi, Ika Nur; Pawanis, Zulfayandi; Yamani, Laura Navika; Pratiwi, Eskarani Tri; Nursalam, Nursalam; Ramoo, Vimala (Nurse Media Journal of Nursing, 2025)
Background: Diabetic Peripheral Neuropathy (DPN) is a common complication of type 2 diabetes mellitus (T2DM) and is closely linked to poor glycemic control. However, little is known about how environmental and lifestyle differences between urban and rural settings affect the risk of DPN.Purpose: This study aimed to identify and compare the risk factors of DPN among T2DM patients living in rural and urban areas.Methods: A comparative cross-sectional design with purposive sampling was used to recruit 156 T2DM patients from both urban (Surabaya) and rural (Lamongan) areas of East Java, Indonesia. Data were collected using the Vascular Quality of Life-6 (VQ-6), Diabetic Neuropathy Symptom (DNS), Diabetic Neuropathy Examination (DNE), and Ankle-Brachial Index (ABI). Logistic regression was performed, with a significance level set at p<0.05.Results: The mean age of rural participants was 55.8 years, slightly younger than that of urban participants. Urban residents had higher levels of education (37.7%) but engaged less in regular physical activity (51.9%). The risk of DPN differed significantly between rural and urban participants. Vascular function (ABI, OR = 4.526, range = 0.7–4.00), peripheral nerve symptoms (DNS, OR = 2.838, range = 0–2), neurological deficits (DNE, OR = 1.571, range = 0–5), and neuropathy-related quality of life (VQ-6, OR = 0.663, range = 0–24, p=0.020) were more pronounced among rural participants.Conclusion: Rural T2DM patients are at greater risk of DPN due to vascular and neuropathic complications, combined with sociodemographic disadvantages. These findings highlight the importance of early detection and tailored education programs for rural communities to prevent and manage DPN.